Efficient finite element electromagnetic analysis of antennas and microwave devices : the FE-BI-FMM formulation and a posteriori error estimation for p adaptive analysis - Botha, Matthys Michiel (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2002.